In Vitro and Ex Vivo Evaluation of Capparis spinosa Extract to Inactivate Protoscoleces During Hydatid Cyst Surgery - Mahmoudvand, Hossein; Khalaf, Amal K.; Beyranvand, Mania (Current Drug Discovery Technologies, 2021)
Background: Hydatidosis is one of the most dangerous zoonosis diseases in the world caused by the larval stage of the broad-worm or Echinococcus granulosus parasite. Today, cysts’ rupture or content leakage during surgery and involvement of organs adjacent to the organ involved, and consequently secondary cysts, are the major concern for hydatid cyst surgeons. Therefore, using scolicidal substances such as hypertonic saline 20%, silver nitrate and formalin has been considered to reduce the risk of protoscoleces spread and recurrence of disease in recent years. The current work was designed to assess the antiparasitic effects of Capparis spinose L. extract against hydatid cyst protoscoleces. Methods: Collected protoscoleces from liver fertile hydatid cysts of infected sheep were exposed to the different concentrations of the essential oil (150, 300, 600 mg/mL) for 5-60 min in vitro and ex vivo. Then by using the eosin exclusion assay, the viability of protoscoleces was studied. The primary phytochemical analysis of the C. spinosa extract was done to assess the presence of tannins, alkaloids, saponins, flavonoids, terpenoids and glycosides. Results: C. spinosa extract exhibited a powerful protoscolicidal activity in vitro so at the dose of 300 and 600 mg/ml, it entirely eliminated the parasite after 10 and 5 minutes; whereas at lower doses, it demonstrated weak protoscolicidal activity. In ex vivo assay, no similar effect to in vitro assay was observed, so more time was required to show a potent protoscolicidal activity. C. spinosa extract, at the concentrations of 300 and 600 mg/mL after an exposure time of 20 and 12 min, killed 100% of protoscoleces within the hydatid cyst, respectively. The findings of primary phytochemical screening of the C. spinosa extract demonstrated the existence of flavonoids, tannins, terpenoids, glycosides and alkaloids in this plant. Conclusion: The obtained results in vitro and ex vivo exhibited potent protoscolicidal effects of C. spinosa extract particularly at the concentrations of 600 and 300 mg/ml, which entirely eliminated the parasite after 5-20 min exposure. However, more supplementary works are required to verify these findings through assessing in animal models and clinical subjects.
Keywords: mortality